Mobile learning by English literature students: the role of user satisfaction - Ibtihal Hassan Mussa; Nurhasmiza Abu Hasan Sazalli; Zainudin Hassan (Institute of Advanced Engineering and Science, 2022)
The purpose of this study is to determine the predictors of using mobile learning (ML) among English literature students in Iraq. This study assumes that variables of UTAUT such as effort expectacny (EE) and performance expectancy (PE) as well as the subjective norms (SN) from theory of planned behavior (TPB) will affect the behavioral intention (BI) to use ML. BI and availability (FC) will affect the actual use (AU). In addition, user satisfaction is proposed as a mediating variable between PE, EE, and SN with BI. Data of this study was collected using a questionnaire from 240 undergraduate students. The data was analyzed using PLS. The findings showed that PE, EE and SN are important factors for the BI of ML. BI and FC significantly affected the AU. User satisfaction mediated only the effect of PE and EE on BI. Easier processes and instruction must be provided by univeristies to enhance the adoption of ML among English literature students.